Current Perspective of Diagnostic and Treatment of Rabies: A Literature Review - Pratama, Nauval Lazuardi; Rahmadinie, Amalia (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
Background. Rabies is a zoonotic disease caused by the rabies virus (RABV) from the Lyssavirus genus. Transmitted through saliva, typically via bites or scratches, it causes fatal neurological disorders if untreated. Annually, rabies claims 59,000 lives, with most cases in rural Africa and Asia, where dogs are the primary reservoirs. Despite available vaccines, low coverage in resource-limited settings makes rabies a persistent public health issue. Effective prevention requires vaccination programs, public awareness, and animal population control. Methods. This study was conducted through a literature review using PubMed and Google Scholar as primary sources. Relevant peer-reviewed articles and research papers on rabies epidemiology, clinical features, pathophysiology, and management published in the last five years (2019–2024) were selected. Keywords such as